Into the woods - Sondheim, Stephen; Lapine, James (Theatre Communications Group, 1989)
Interwoven with such classics as Cinderella, Jack and the Beanstalk, and Little Red Ridinghood, is the story of the baker and his wife, whose longing for a child is thwarted by a mischievous witch who lives next door.